Compostos fenólicos e atividade antioxidante de Leiothrix flavescens (Bong.) Ruhland (Eriocaulaceae) - Silva, M. A. [UNESP]; Sumitami, J. S A [UNESP]; Vilegas, Wagner [UNESP]; Santos, Lourdes Campaner dos [UNESP] (My University, 2007)
This paper describes a chemical investigation (by high-speed counter-current chromatography) of an extract in methanol of the capitula (flower-heads) of the endemic Brazilian herb Leiothrix flavescens (Bong.) Ruhland (Eriocaulaceae). Fractionation of this extract by preparative chromatography and identification of the isolated compounds by spectrometric methods (IR, UV, ESI-MS, NMR) led to the identification of flavones (apigenin, luteolin and 6-methoxyluteolin) and 1,3-di-O-feruloyl glycerol. The antioxidant activity of the extract was determined by DPPH reduction and the total phenolic content by the Folin-Ciocalteau assay. It was found that the methanolic extract of L. flavescens possesses strong antioxidant activity. Additionally, the chemical profile provided useful data for a discussion of the taxonomy of the Eriocaulaceae.

O presente estudo químico foi realizado com extrato metanólico de Leiothrix flavescens (Bong.) Ruhland (Eriocaulaceae) por HSCCC. Fracionamento do extrato metanólico dos capítulos de L. flavescens por métodos cromatográficos preparativos e identificação das substâncias isoladas por (IV, UV, RMN) forneceu as flavonas apigenina, luteolina e 6-metoxiluteolina e o 1,3-di-Oferuloilglicerol. O extrato metanólico de L. flavescens foi avaliado quanto à sua atividade antioxidante utilizando- se o reagente de DPPH, enquanto que a quantificação de fenóis totais foi determinada utilizando-se o reagente de Folin-Ciocalteau. Os resultados evidenciaram que o extrato metanólico dos capítulos L. flavescens possui uma significativa atividade antioxidante. Estes resultados permitiram aprofundar a discussão taxonômica da família Eriocaulaceae. Palavras-chave: Eriocaulaceae; Leiothrix; HSCCC; atividade antioxidante.
Phenolic compounds and antioxidant activity in extract of Leiothrix flavescens (Bong.) Ruhland (Eriocaulaceae)
Keywords: Antioxidant activity; Eriocaulaceae; HSCCC; Leiothrix; 1,1 diphenyl 2 picrylhydrazyl; 1,3 di o feruloylglycerol; 6 methoxyluteolin; apigenin; flavone derivative; Leiothrix flavascens extract; luteolin; methanol; phenol derivative; plant extract; unclassified drug; antioxidant activity; assay; counter current chromatography; drug identification; electrospray mass spectrometry; flower head; folin ciocalteau assay; herb; infrared spectrometry; Leiothrix flavascens; nuclear magnetic resonance spectroscopy; plant taxonomy; reduction; spectrophotometer